RabA2b Overexpression Alters the Plasma-Membrane Proteome and Improves Drought Tolerance in Arabidopsis - Ambastha, Vivek; Matityahu, Ifat; Tidhar, Dafna; Leshem, Yehoram (Frontiers in Plant Science, 2021)
Rab proteins are small GTPases that are important in the regulation of vesicle trafficking. Through data mining, we identified RabA2b to be stress responsive, though little is known about the involvement of RabA in plant responses to abiotic stresses. Analysis of the RabA2b native promoter showed strong activity during osmotic stress, which required the stress hormone Abscisic acid (ABA) and was restricted to the vasculature. Sequence analysis of the promoter region identified predicted binding motifs for several ABA-responsive transcription factors. We cloned RabA2b and overexpressed it in Arabidopsis. The resulting transgenic plants were strikingly drought resistant. The reduced water loss observed in detached leaves of the transgenic plants could not be explained by stomatal aperture or density, which was similar in all the genotypes. Subcellular localization studies detected strong colocalization between RabA2b and the plasma membrane (PM) marker PIP2. Further studies of the PM showed, for the first time, a distinguished alteration in the PM proteome as a result of RabA2b overexpression. Proteomic analysis of isolated PM fractions showed enrichment of stress-coping proteins as well as cell wall/cuticle modifiers in the transgenic lines. Finally, the cuticle permeability of transgenic leaves was significantly reduced compared to the wild type, undoubtedly playing suggesting that it plays a role in its drought resistant properties. Overall, these data provide new insights into the roles and modes of action of RabA2b during water stresses, and indicate that increased RabA2b mediated PM trafficking can affect the PM proteome and increase drought tolerance.